An Overview Review of Understanding the Need for Adolescents Sexual and Reproductive Health Interventions - V.S. Leena; V. Vijayalakshmi (Human Research in Rehabilitation, 2024)
Adolescents are the most vulnerable group, who are denied to access information and guidance related to sexual and reproductive health needs because of the social taboos that lead them to encumbrances. This review study helps to understand the different perspectives of sexual and reproductive health based on cultural, sociological, physiological, and economical aspects. The paper explains sexuality from the theoretical perspectives. Adolescence is the transitional stage where physiological, biological, and psychological changes occur, at the same time proper knowledge about sexual and reproductive health should be provided with importance of sexual and reproductive health interventions. It intricates the availability and effectiveness of adolescent sexual and reproductive health (ASRH). The methodology is a systematic review with PRISMA guidelines sourced from various databases of PubMed databases, Research Gate, Science Direct, BMC Public Health, Web of Science, SAGE, Scopus, WHO library, and other websites relevant to this study. The recent literature highlighted the importance of sexual and reproductive health interventions among adolescents. The study has concluded with the findings impact of Adolescent Sexual and Reproductive Health (ASRH) intervention programmes and to develop an increase in effective ASRH programmes, which will help the adolescents to know the importance of sexual hygiene and reproductive hygiene.